Phenolic compounds and antioxidant activities of grape canes extracts from vineyards - Ju, Yanlun; Zhang, Ang; Fang, Yulin; Liu, Min; Zhao, Xianfang; Wang, Hua; Zhang, Zhenwen (Spanish Journal of Agricultural Research, 2016)
Grape canes are the main agro-wastes from vineyards. This work studied the antioxidant activities of the defatted methanolic extracts (ME) of canes from 11 genotypes: 5 Vitis vinifera widely known cultivars and 6 Chinese wild varieties from three species (V. amurensis, V. davidii, and V. pentagona) and the antioxidant activities of the ME’s chloroform fractions (CF), ethyl acetate fractions (EAF) and water fractions (WF). Among ME and its three fractions, EAF’s total phenolic contents (TPC) and total flavonoid contents (TFC) were the highest, at 586 mg/g of gallic acid equivalent and 320 mg/g of quercetin equivalent, respectively. The antioxidant power of the fractions/extracts was in the order EAF > ME > WF > CF, based on the DPPH radical-scavenging power and ferric-reducing antioxidant activity, while the order was EAF > CF > WF >ME based on the β-carotene-linoleic acid bleaching activity. Methanolic extracts demonstrated the strongest Fe2+-chelating activity. The antioxidant activities of the extracts/fractions generally correlated with the TPC and TFC in all assays, except with the Fe2+-chelating test. Grape canes from V. davidii had the highest TPC, TFC and antioxidant activities compared with those from other grape species. Catechin, epicatechin and trans-resveratrol were the predominant phenolic components of fractions/extracts. In light of these valuable bioactivities, grape canes from annual pruning practice considered as waste material have good commercial potential for utilization as a promising natural antioxidant in the food, pharmaceutical and cosmetic industries, given its low cost and availability in large amounts. <!–EndFragment–>